PENATALAKSANAAN PENUTUPAN DIASTEMA SENTRAL SETELAH PENCABUTAN GIGI MESIODENS - Sutjiati, Rina (Fakultas Kedokteran Gigi Universitas Jember, 2011)
The treatment of mesiodens for children has to be done completely and continuously. Management of the treatment of mesiodens teeth can be done by extraction or without extraction. Diastema central can be closed earlier by using orthodontic appliance after extracting mesiodens teeth for children.